PEER INTERACTION IN LAGUANGE LEARNING AT SMAN 1 GALIS PAMEKASAN - Mohammad Amiruddin; Evha Nazalatus Sa’adiyah Sy; Muh. Darrin Zuhri (Journey: Journal of English Language and Pedagogy, 2022)
This study is to finding out the ways teachers creating the peer interaction of students and the effect of the peer interaction of students on language learning at SMAN 1 Galis Pamekasan. This study facilitates the students having interaction and sharing their thought in English as well as it becomes beneficial input in language learning. This study is a qualitative research by using descriptive case study approach. This study describes in details the methods of the teachers promote student peer contact as well as the impact of student peer interaction on language acquisition. The participants of this study are the students and the teachers at SMAN 1 Galis; Convince sampling is used in this study . Observation and interview are conducted to get the data of peer interaction and the influences of it in language learning. The results show that the way the teacher creates peer interacts with restricted English interaction and full English interaction. Peer Interaction in learning acts as an input in learning English and as a stimulus that can increase students' motivation to interact using English.